18F-Labeling Using Click Cycloadditions. (27th May 2014) - Kettenbach, Kathrin; Schieferstein, Hanno; Ross, Tobias L.
Abstract : Due to expanding applications of positron emission tomography (PET) there is a demand for developing new techniques to introduce fluorine-18 (t 1 / 2 = 109.8 min). Considering that most novel PET tracers are sensitive biomolecules and that direct introduction of fluorine-18 often needs harsh conditions, the insertion of 18 F in those molecules poses an exceeding challenge. Two major challenges during 18 F-labeling are a regioselective introduction and a fast and high yielding way under mild conditions. Furthermore, attention has to be paid to functionalities, which are usually present in complex structures of the target molecule. The Cu-catalyzed azide-alkyne cycloaddition (CuAAC) and several copper-free click reactions represent such methods for radiolabeling of sensitive molecules under the above-mentioned criteria. This minireview will provide a quick overview about the development of novel 18 F-labeled prosthetic groups for click cycloadditions and will summarize recent trends in copper-catalyzed and copper-free click 18 F-cycloadditions.